KAJIAN FISIOLOGIS TANAMAN TOMAT TERHADAP PENAMBAHAN UNSUR HARA Fe DAN N - Sumiyati Tuhuteru (Jurnal Agroekoteknologi, 2018)
Nitrogen is the most dominant element affecting plant growth compared to other elements. Whereas Fe is rare. The occurrence of symptoms in parts of the plant (especially leaves) is then expressed as a lack of Fe availability because of the imbalance in the Fe availability with Calcium in the soil which is excessive on Calsium and alkaline. The purpose of this research was to knowing the symptoms of agility and poisoning of macro and micro-nutritional elements on physiological properties and growth of tomato plants. The research had been conductedin January - March 2017 at Green House and Laboratory of Agriculture of STIPER Petra Baliem Wamena, Papua. The treatments were assigned in Completely Randomized Design with addition of N and Fe i.e. without Fe (-Fe), 3x Fe (3Fe), 3x N, treatment of N + Fe (complete) and without N (-N), then followed by Duncan's multiple ranges test at level 0.5. The results showed the treatment of 3xN and 3xFe of the Hoagland dose 2 solution had not reached the maximum level so that it had not shown any toxic symptoms, symptoms of N deficiency were chlorosis (pale green to yellow) in old leaves, stunted growth, and more leaf necrosis bottom in cases of severe N deficiency, and 3xFe treatment of Hoagland 2 doses resulted in the lowest plant height estimated due to iron toxicity. Keywords: Hara, Physiology, Pomatoes